ELASTICITY EXPLORATION OF TALI BAMBOO (GIGANTOCHLOA APUS)A CASE STUDY IN DEVELOPING ROCKING TOY - Prawira Herijadi, Farhandika
Bamboo is an abundant plant and material in Indonesia, and tali bamboo (Gigantochloa apus) is one of the common types. This material is known for its natural elasticity. From this property, various bamboo processing techniques have emerged, such as lamination, bending, coiling, and weaving. However, the dynamic use of bamboo's elasticity is still uncommon. Therefore, this research discusses how bamboo's elasticity can be dynamically utilized and applied in a product. The focus of this study is on the exploration and experimental methods of bamboo material to find the appropriate bamboo processing techniques to achieve this goal. Through material experiments, it can be concluded that each technique used has different impacts on the final result. The rebounding power, damping capacity, and flexibility of bamboo are greatly influenced by bending, lamination thickness, and shape. The developed product from these experiments is a rocking toy, where elasticity can be utilized to create a bouncing and flexible structure, unlike conventional rocking toys. This final product is expected to aid in the development of children's motor skills and open opportunities for the future development of bamboo products with dynamic usage.